The moral imagination of R.K. Narayanan : a study of the influences of the Upanishads - Rajoo, Krishnaweni (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2011)
Some significant research has already been carried out upon selected works of Narayan in the realm of holiness, religion and its symbols, Indian mythology and moksha (liberation). Therefore it is fitting to look at the novels of this writer in the dominion of the Hindu religious philosophy of the Upanishads. The basic elements in this author's writing indicate straightforwardness, honesty, freedom, transmigration, ethics and traditional practices, which can be analysed in the sphere of the Upanishads. This study aims to elucidate some elements pertaining to the spirituality of the Upanishads in the works of the Indian novelist in English, R.K. Narayan. It argues that the unique quality of Narayan's writings, his plot and characterisation indicate the simplicity imbibed from the teachings of the Upanishads. The study highlights different areas of concern to Narayan and some of them are the search for truth and purity, spirituality, integration and liberation. This study uses the Upanishads as a philosophical framework of analysis. The Upanishads advocate a monistic religion; it equates the Atman in mankind as a spark of Brahman (the supersoul) and it desires humans to strive to be perfect, to realise that they are on a quest towards realising God. The indication is that as a writer, Narayan subsumes to the principles of the Indian philosophy of the Upanishads in the thematic ideals of his novels. This study investigates seven of his fifteen novels as subscribing to the tenets of the Upanishads in the realm of disposition and gravity. The study also strives to demonstrate that Narayan's key themes, characterisation and stratagem all points towards a spiritual propensity of the Upanishads. This study analyses the novels pertaining to the major themes running through them. The chapters of the thesis will be divided into the novels to be investigated. The most relevant novels of Narayan will be investigated and appropriated into the corresponding chapters, chronologically. The novels of Narayan examined in this study indicate that the characters are not only simple or basic in the mode of their lives, but are also positive about life no matter if the world seems to be crumbling around them. They also have an infallible way of falling back into track and to keep on looking forward towards the end of their lives, akin to the person for whom the way (sadhana) is as important as the end (moksha).